2020–2021 Vegetable Production Handbook: Chapter 9. Leafy Vegetable Production - Ramdas Kanissery; Richard N. Raid; Johan Desaeger; Julien Beuzelin; Christian F. Miller; Peter Dittmar (EDIS)
This chapter covers lettuce, endive, escarole, and spinach cultivation.